FIGO analysis of research priorities in hyperglycemia in pregnancy. (November 2018) - McIntyre, David; Desoye, Gernot; Dunne, Fidelma; Simeoni, Umberto; Visser, Gerard H.A.; Kapur, Anil; Hod, Moshe
Abstract: Hyperglycemia in pregnancy (HIP) is recognized as a major underlying cause of pregnancy complications and a contributing cause to health risks throughout the subsequent life of both mothers and babies, with amplification of the global epidemic of non-communicable diseases. Although some aspects of these associations are well described, detailed understanding of basic pathophysiologic mechanisms is lacking. Improved fundamental scientific knowledge must be developed to allow logical strategies for prevention and treatment. During pregnancy, much work is required to replace current empirical approaches to diagnosis and treatment of HIP with evidence based protocols, pragmatically adapted to differing health care and health economic contexts. Further, a life cycle approach to HIP, the risk of immediate pregnancy complications and later health risks to mother and baby must be developed and implemented across a wide range of health care environments. This document aims to outline key focus areas for further basic, epidemiologic, clinical and implementation research in this important area.